The Restoration of Russia with United Kingdom's Diplomatic Realtions in 2018 - Imtiyaz Budi Raghdhany; Djoko Susilo; Fuat Albayumi (Journal of Social and Political Science)
The relationship between Russia and Britain experienced tensions since the cold postwar and became less harmonious since the case of Alexander Litvinenko in 2006. Alexander Litvinenko is a former Russian agent who moved to England and was found dead because of poison in London. In addition to the case of Alexander Litvinenko cause the relationship of both countries deteriorated because of the case of Crimea in the year 2014, Russia intervened in the Brexit referendum in 2016. The relations of the two countries suffered a strain back in 2018. In 2018 Sergei Skripal and his son Yulia Skripal were found unconscious of poison in his body while walking in the city of Salisbury, London. Consequently the two countries experienced a diplomatic crisis. This study was conducted to know the efforts made by the Russians to improve diplomatic relations with England in the year 2018.